Around the problem of political freedom: republicanism and liberalism - Estrada-Pérez, Luis F. (2020)
In the present work it is made up of five parts. The first is dedicated to presenting the problem of the exercise of freedom and the consequences that it entails both in the republican and in the liberal model and, of course, it’s different variants. The second part works on the importance of promoting civic values ​​in republicanism, as well as the counterproductive consequences. The third part problematizes if a liberal model can also arrive at a more cooperative and participative position. A distinction is made between psychological egoism (EP), ethical egoism (EE) and rational egoism (ER), to analyze which of the latter fits the liberal model. Finally, in the last part, it is proposed that a cooperative version from a liberal perspective is based, following Nozick, on the «ethical push» and the search to make our lives meaningful. Our main hypothesis is that ethical motivation is what enables a commitment to the public question both in the liberal version and in the republican position.